PENGGUNAAN SHAPES TOOLS PADA MICROSOFT WORD UNTUK MENINGKATKAN KEMAMPUAN MENGGAMBAR COMIC STRIPS SISWA KELAS VIII SMP NEGERI 1 PACITAN - Ninik Setyawati (BBPPMPV Seni dan Budaya Yogyakarta, 2021)
Students’ boredom of drawing comic strips using manual techniques and the constraining condition of digital drawing devices are the results of problem identification that bring about the conduct of the current research. Hence, the research question proposed is how students’ ability in drawing comic strips can be improved by introducing them the ‘shapes tools’ available in Microsoft Word. Classroom action research of Kemmis and McTaggart model (1990) is employed to answer the research question with the research subjects of the eighth graders of SMP Negeri 1 Pacitan involved in two research cycles for three months comprising four steps in each cycle, namely (1) planning, (2) implementing, (3) observing, and (4) reflecting. Research results demonstrate that in pre-cycle condition, the average score of comic strips drawing skill is below the score of minimum mastery criteria. Having been introduced with shapes tools of Microsoft Word in research cycle 1 and 2, the average score of students’ drawing skill and the classical mastery score increase significantly. The use of ‘shapes’ and ‘shapes styles’ offers some good points in color processing: the work resembles a three-dimensional form, the process is fast, the work is easy to edit and to duplicate, the file size is small, and the work is relatively equivalent to graphic applications.